2015
DOI: 10.1111/1462-2920.12719
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of protein kinase PsSRPKL, a novel pathogenicity factor in the wheat stripe rust fungus

Abstract: As in other eukaryotes, protein kinases (PKs) are generally evolutionarily conserved and play major regulatory roles in plant pathogenic fungi. Many PKs have been proven to be important for pathogenesis in model fungal plant pathogens, but little is currently known about their roles in the pathogenesis of cereal rust fungi, devastating pathogens in agriculture worldwide. Here, we report on an in planta highly induced PK gene PsSRPKL from the wheat stripe rust fungus Puccinia striiformis f. sp. tritici (Pst), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 73 publications
0
63
0
Order By: Relevance
“…For example, Pst_12394 was significantly up‐regulated at 18 h post‐inoculation (hpi), with a peak at 48 hpi. In general, 18–48 hpi is considered an important stage for infectious hypha and haustorium formation, and this early stage of infection is critical for pathogen colonization (Cheng et al , ). Expressions of Pst_16188 and Pst_19493 were up‐regulated from urediospore germination, peaking at 256 hpi (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Pst_12394 was significantly up‐regulated at 18 h post‐inoculation (hpi), with a peak at 48 hpi. In general, 18–48 hpi is considered an important stage for infectious hypha and haustorium formation, and this early stage of infection is critical for pathogen colonization (Cheng et al , ). Expressions of Pst_16188 and Pst_19493 were up‐regulated from urediospore germination, peaking at 256 hpi (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, host-induced gene silencing (HIGS) has been developed and has proven to be a useful tool to study genes in obligate biotrophic pathogens (Nowara et al, 2010;Yin and Hulbert, 2015). Several Pst genes were shown to be important for rust pathogenicity or fungal growth using the barley stripe mosaic virus (BSMV)-mediated HIGS system Zhang et al, 2012;Cheng et al, 2015;Tang et al, 2015;Cheng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual reproduction is the primary process contributing to the origin of new races with combined virulence genes and diversification of stripe rust pathogens (Zhao et al ., ). Although some virulence‐related genes have been described in Pst (Cheng et al ., ; Liu et al ., ; Tang et al ., ), fewer studies have documented the genes that are involved in mating in Pst . A previous study has reported that the orthologue STE12 , together with other components, contributes to the regulation of fertility in sexual crosses in heterothallic fungi, such as S .…”
Section: Discussionmentioning
confidence: 99%